2011
DOI: 10.1097/meg.0b013e328340c451
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C testing and treatment among active drug users in Amsterdam

Abstract: In a multidisciplinary setting, HIV-negative drug users with chronic HCV infection can be treated successfully despite active drug or alcohol use and psychiatric diseases. Therefore, access to HCV therapy using an integrated approach should be increased for this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
35
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(35 citation statements)
references
References 50 publications
0
35
0
Order By: Relevance
“…The 25 studies included one randomised controlled study [16], three cross-sectional studies [17-19], 11 retrospective cohort studies [20-30] and 10 prospective cohort studies [31-40]. Ten of the studies took place at drug treatment clinics, five at hepatitis clinics, and ten in other types of settings.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 25 studies included one randomised controlled study [16], three cross-sectional studies [17-19], 11 retrospective cohort studies [20-30] and 10 prospective cohort studies [31-40]. Ten of the studies took place at drug treatment clinics, five at hepatitis clinics, and ten in other types of settings.…”
Section: Resultsmentioning
confidence: 99%
“…The HCV antibody-positive treatment uptake level reflects the number of study participants who received treatment as a proportion of the number of study participants known to have antibodies for hepatitis C. Ten studies [19,22,24,26,32,35,36,38-40] reported treatment uptake in relation to HCV antibody-positive status (Table 2). Among groups of study participants who were HCV antibody-positive, treatment uptake ranged from 3% to 64% (median: 17%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although ever/current drug injectors have treatment efficacy and safety outcomes that are comparable to those for people with no history of drug use [15,66-70], and successful treatment could reduce the likelihood of HCV transmission among PWID by eliminating potential sources of infection [9], international and national treatment guidelines historically have excluded PWID, particularly current injectors, from being treated for hepatitis C [15,70,71]. In 2011, however, the Clinical Practice Guidelines of the European Association for the Study of the Liver (EASL) were revised to endorse the provision of HCV treatment to certain PWID based on an individual approach [72].…”
Section: Discussionmentioning
confidence: 99%
“…3 The experience of some European countries has shown that access of PWID to HCV therapy (including DAA) and scaling up HCV treatment is feasible using an integrated multidisciplinary approach. [17][18][19] The need for psychiatric evaluation is enforced by most of the Medicaid providers. This requirement is implemented for anyone who has used illicit drugs, or any psychotropic medication in their lifetime.…”
Section: Discussionmentioning
confidence: 99%